Advances in molecular diagnosis and therapeutics in nephrotic syndrome and focal and segmental glomerulosclerosis. Issue 3 (May 2018) - Sharif, Bedra; Barua, Moumita
Abstract : Purpose of review: The widespread adoption of next-generation sequencing by research and clinical laboratories has begun to uncover the previously unknown genetic basis of many diseases. In nephrology, one of the best examples of this is seen in focal and segmental glomerulosclerosis (FSGS) and nephrotic syndrome. We review advances made in 2017 as a result of human and molecular genetic studies as it relates to FSGS and nephrotic syndrome. Recent findings: There are more than 50 monogenic genes described in steroid-resistant nephrotic syndrome and FSGS, with seven reported in 2017. In individuals presenting with FSGS or nephrotic syndrome before or at the age of 18 years, the commonest genes in which a mutation is found continues to be limited to only a few including NPHS1 and NPHS2 based on multiple studies. For FSGS or nephrotic syndrome that presents after 18 years, mutations in COl4A3/4/5, traditionally associated with Alport syndrome, are increasingly being reported. Despite the extensive genetic heterogeneity in FSGS, there is evidence that some of these genes converge onto common pathways. There are also reports of in-vivo models exploring apolipoprotein 1 biology, variants in which account for part of the increased risk of nondiabetic kidney disease in African-Americans. Finally, genetic testing has several clinical uses including clarification of diagnosis and treatment; identification of suitable young biologic relatives for kidney donation; and preimplantation genetic diagnosis. CRISPR gene editing is currently an experimental tool only, but the recent reports of excising mutations in embryos could be a therapeutic option for individuals with any monogenic disorder in the future. Summary: Sequencing efforts are bringing novel variants into investigation and directing the efforts to understand how these lead to disease phenotypes. Expanding our understanding of the genetic basis of health and disease processes is the necessary first step to elaborate the repertoire of therapeutic agents available for patients with FSGS and nephrotic syndrome.